ON STUDY OF TRAINING SUCCESS MATHEMATICAL MODEL AND OF CREATING PSYCHOLOGICAL DATABASE FOR MODEL TESTING - Galina Victorovna Belushkina; Marina Vladimirovna Vasilchenko; Natalya Alexandrovna Lopatkina; Olga Elfatovna Khafizyanova (Advanced Engineering Research)
The mathematical model of training success based on the factor analysis method is presented. The psychological characteristics of the students obtained as a result of the conducted experiment are considered as factors of this method. The academic progress of students determined by the examination record is chosen as a resultant factor. The psychological experiment was conducted in DSTU groups of students of specialty 030300 by means of R. Cattell's 16 PF test. The test results allowed making up a sufficiently complete “psychological portrait” of the second-year students which has been served as a good database for the consequential development of the training success mathematical model. A two-way analysis of variance has been applied to calculate the model. Each binary pair of factors is classified under two ranking levels: low level — high level. An example of the model analysis is given, the impact of various factor pairs and their combinations on training success is analyzed. Having a sufficiently complete database, it is possible to use the presented model, and to facilitate the educational process for teachers and students after revealing the patterns.